Parameter Optimization of AA6061-AA7075 Dissimilar Friction Stir Welding using the Taguchi Method - L. H., Shah; Nur Farhana, Zainal Ariffin; A. R., Razali (Trans Tech Publications, Switzerland, 2015)
In this study, the Taguchi method was utilized to determine the optimum process parameters for dissimilar friction stir welding between AA6061 and AA7075 aluminium alloys. The Taguchi L9 orthogonal array and optimization approach was applied on three levels of three critical factors, namely rotational speed, transverse speed and tool tilt angle. The optimum levels of process parameters were determined through the Taguchi parametric design approach. Through the parameter analysis, the predicted value of the dissimilar joint’s tensile strength was calculated to be 209.7 MPa, which is in close proximity to the experimental data (219.6 MPa) with 4.5% error. It can be concluded that a high tensile value of 219.6 MPa was achieved using 1000 rpm rotational speed, 110 mm/min travel speed and 3 ̊ tilt angle.